Podcast As Reflection Platform for Promoting EFL Preservice Teachers’ English Skill, Sense of Motivation, And Critical Thinking - Muhammad Hafizh Fariadhi; Yustian Fadlan Fadillah; Rana Rahmat Hidayat; Apandi Apandi; Utut Kurniati (Universitas Muria Kudus, 2025)
This study investigated how pre-service EFL (English as a Foreign Language) teachers perceived the use of podcasts as a reflective tool to improve their motivation, critical thinking, and English language skills. The primary goal was to find out how podcasts can reinforce language competencies, reflective practice, professional development, and richer and deeper learning. Case study was the method used whereby 34 students of a private Indonesian university participated in a two-week podcasting exercise. Semi-structured interviews and surveys were the methods used to gather data. It revealed that the podcasts encouraged self-expression, critical reflection, and growing confidence alongside linguistic skill, in terms of listening and speaking. In addition to this, participants reported that freedom to learn alone had increased motivation and satisfaction levels. The study makes several recommendations for improving the use of podcasts in EFL contexts, including making sure the content is credible, incorporating interactive elements to prevent passive learning, and completely incorporating podcasts into the EFL curriculum. It is recommended that future studies investigate the use of podcasts in diverse educational contexts and look into their long-term effects. All things considered, the study shows that podcasts are a versatile and useful tool that can enhance future EFL teachers' language learning and professional development.Â